Intellectual capital, governmental presence, and firm performance of publicly listed companies in Malaysia - Qian, Long Kweh; Irene, Wei Kiong Ting; Hanh, Le Thi My; Zhang, Cheng (Inderscience Enterprises Ltd., 2019)
This study analyses the association between intellectual capital (IC) and firm performance and the differential impact of IC on firm performance between firms with and without government ownership. Data on the top 200 companies listed on the Malaysian Stock Exchange from 2010 to 2015 are used to estimate the value added intellectual coefficient (VAIC™) model. The ordinary least squares results indicate that firms with and without government ownership differ in firm performance and IC. Capital employed efficiency (CEE), human capital efficiency (HCE), and total IC have significantly positive impacts on firm performance. However, the significantly positive impacts of CEE and HCE on firm performance are only found in firms without government ownership. The significantly negative effect of government presence is confirmed in the pooled data analysis, whereby only CEE is significantly related to firm performance for firms with government ownership.